The Classical Gardens of Shanghai - Bryant, Shelly (RAS China in Shanghai series of China Monographs., 2016)
In The Classical Gardens of Shanghai, Shelly Bryant looks at five of Shanghai's remaining classical gardens through their origins, changing fortunes, restorations, and links to a wider Chinese aesthetic. Shanghai's classical gardens are as much text as space; they exist in art, poetry, and literature as much as in stone, rock, and earth. But these gardens have not remained static entities. Rather, they have been remodeled constantly since their inception. This book reflects this process within the constancy of traditional Chinese horticulture and reveals Shanghai's remaining classical gardens as places representing wealth and social status, social and dynastic shifts, through falling family fortunes and political revolutions to search for a recovery of China's ancient culture in the modern day.